Redistributional preferences and imposed institutions - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2006)
To what extent do imposed institutions shape preferences? We consider this issue by comparing the market-versus-state attitudes of respondents from a capitalist country, Finland, and an ex-communist group of Baltic countries, and by arguing that the period of communist rule can be viewed as an 'experiment' in institutional imposition. We find that, consistent with some earlier related work, citizens from ex-communist countries tend to be more supportive of state ownership than respondents from capitalist economies. However, they also favor increasing inequality and competition as the means to enhance incentives. We conclude that, in some important relevant dimensions, institutional imposition (which lasted for about 50 years) had a limited effect on preferences. The lessons for Latin America are straightforward.
Keywords: P30; P51; D30; D02; I31; 330; Institutions; markets versus state; redistributional preferences